Silent mutations in the phenylalanine hydroxylase gene as an aid to the diagnosis of phenylketonuria. Issue 10 (October 1991) - Kalaydjieva, L; Dworniczak, B; Aulehla-Scholz, C; Devoto, M; Romeo, G; Sturhmann, M; Kucinskas, V; Yurgelyavicius, V; Horst, J
Abstract : Direct sequencing of the phenylalanine hydroxylase (PAH) gene indicated the existence of silent mutations in codons 232, 245, and 385, linked to specific RFLP haplotypes in several Caucasian populations, namely Germans, Bulgarians, Italians, Turks, and Lithuanians. All three mutations create a new restriction site and can be easily detected on PCR amplified DNA. The usefulness of the silent mutations for diagnostic purposes depends on the haplotype distribution in the target population. The combined analysis of these markers and one or two PKU mutations forms a simple panel of diagnostic tests with full informativeness in a large proportion of PKU families, which helps to avoid the problems of genetic heterogeneity and of prenatal genomic Southern blot analysis.